Kafa`ah dalam Perkawinan Menurut Pemikiran TGKH. M. Zainuddin Abdul Madjid (1898-1997) - Munawirsazali, Munawirsazali (ASASI: Journal of Islamic Family Law, 2022)
TGKH. M. Zainuddin Abdul Majid is a contemporary cleric from West Nusa Tenggara who has great concern for family life, especially with regard to the concept of kafa>`ah in marriage with his solutive offer contained in the book Testament Reflections on New Experiences. Interesting thoughts from TGKH. Muhammad Zainuddin Abdul Majid is when he gives a new perspective in understanding kafa>`ah standards in marriage which cover two areas, namely morals and pure inheritance. TGKH. M. Zainuddin Abdul Majid does not make the area of property, traditional titles based on social status, and beauty the standard of kafa>`ah in marriage. The beginning of the emergence of TGKH's thoughts. M. Zainuddin Abdul Majid departs from the macro conditions of the Muslim community on Lombok Island, West Nusa Tenggara, which has a marriage system based on the existing social class, namely women who have a high social class are not allowed to marry men who have a low social class because both of them not considered to meet the kafa>`ah standard. Therefore, Shaykh Zainuddin wanted to protect women by building a new concept of kafa>`ah standards in marriage which put more emphasis on moral aspects and pure inheritance.